Hubungan Rensponse Time Pelayanan Instalasi Gawat Darurat (IGD) Dengan Tingkat Kepuasan Pasien - Toni Akhirul; Nurul Fatwati Fitriana (Jurnal Keperawatan Muhammadiyah, 2020)
Background: Emergency is a clinical condition of patients who need immediate medical treatment. Response time is the alacrity in treating the patients done by health workers from patients' arrival at the hospital to patients treatment. Response time with standardized treatment alacrity can be a good process of service so the patients will be satisfied.Aim: To find out the correlation between the response time of Emergency Department service and patients' satisfaction level in Wijayakusuma Hospital of Purwokerto.Method: This research used a quantitative method with a cross-sectional observational design. The 94 samples were taken using a purposive sampling technique. The data were collected using a questionnaire and response time observation sheets and analyzed using the Sommersd test.Results: The results from the response time of Emergency Department service of Wijayakusuma Hospital of Purwokerto were fast (81.9%) and slow (18.1%).The patients' satisfaction level showed very satisfied (81.9%), satisfied (6.4%), and not satisfied (11.7%) toward the Emergency Department service. The analysis results between response time and satisfaction level using the Sommersd test showed sig value was 0.001 (p 0.05) and the coefficient correlation value was 0.654 which meant there was a correlation between the response time of the Emergency Department service and patients' satisfaction level with strong correlation power.Conclusion: There was a correlation between the response time of Emergency Department service and patients' satisfaction level with strong correlation power.